2016
DOI: 10.1186/s13045-016-0351-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel extracellular and nuclear caspase-1 and inflammasomes propagate inflammation and regulate gene expression: a comprehensive database mining study

Abstract: BackgroundCaspase-1 is present in the cytosol as an inactive zymogen and requires the protein complexes named “inflammasomes” for proteolytic activation. However, it remains unclear whether the proteolytic activity of caspase-1 is confined only to the cytosol where inflammasomes are assembled to convert inactive pro-caspase-1 to active caspase-1.MethodsWe conducted meticulous data analysis methods on proteomic, protein interaction, protein intracellular localization, and gene expressions of 114 experimentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 54 publications
(96 reference statements)
5
84
0
Order By: Relevance
“…Although the research paper associated with this GEO dataset has not been published from Dr. Luscher’s team in the University Hospital Zurich, Switzerland, based on similar publications on isolation of Tregs [44], CD14 + monocytes and CD66B + granulocytes [45] in coronary thrombi of patients with ACS and microarray profiling [46] from this highly productive team, we were fully convinced that the high quality of GSE19339 dataset and related technologies in coronary thrombus leukocyte isolation and microarray profiling are trustable. In addition, to determine the functional significance of upregulated genes, we examined the subcellular localization of the 15 upregulated genes including FLT1, NRP1, ANGPTL4, NRP2, VEGFA, EPAS1, JAG1, TEK, JUN, NOTCH3, TIE1, KDR, HIF1A, ANGPT2, and PGF using two highly reliable databases (COMPARTMENTS subcellular location database and UniProtKB/Swiss-Prot location database) as we reported [10] (Fig. 6a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the research paper associated with this GEO dataset has not been published from Dr. Luscher’s team in the University Hospital Zurich, Switzerland, based on similar publications on isolation of Tregs [44], CD14 + monocytes and CD66B + granulocytes [45] in coronary thrombi of patients with ACS and microarray profiling [46] from this highly productive team, we were fully convinced that the high quality of GSE19339 dataset and related technologies in coronary thrombus leukocyte isolation and microarray profiling are trustable. In addition, to determine the functional significance of upregulated genes, we examined the subcellular localization of the 15 upregulated genes including FLT1, NRP1, ANGPTL4, NRP2, VEGFA, EPAS1, JAG1, TEK, JUN, NOTCH3, TIE1, KDR, HIF1A, ANGPT2, and PGF using two highly reliable databases (COMPARTMENTS subcellular location database and UniProtKB/Swiss-Prot location database) as we reported [10] (Fig. 6a).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether inflammatory factors assist angiogenic cells in recognizing cardiovascular disease risk factors such as hyperlipidemia, hyperglycemia, obesity, metabolic syndrome, hypertension, smoke, and hyperhomocystemia [7], we recently reported a series of findings on the expression and roles of innate immune/inflammation sensor caspase-1/inflammasome [810] in regulating angiogenic cells, including endothelial cell [1115], Sca-1 + progenitor cell [16, 17]. We also found that CD4 + Foxp3 + regulatory T cells (Tregs) inhibit vascular inflammation [1820] and that Treg-generated newly classified responsive immunosuppressive cytokine interleukin-35 (IL-35) [21] suppresses EC activation [22].…”
Section: Introductionmentioning
confidence: 99%
“…An extracellular role of the inflammasome and its components has already been suggested (Baroja-Mazo et al, 2014;Franklin et al, 2014;Mitra et al, 2015). Moreover, IL-1b, caspase-1, and other inflammasome components have been described to localize to exosomes (Qu et al, 2007) and it was suggested from a meta-analysis of proteomic and protein interaction data that caspase-1 cleaves its substrates to propagate inflammation to neighboring and remote cells in extracellular vesicles (Wang et al, 2016). Moreover, IL-1b, caspase-1, and other inflammasome components have been described to localize to exosomes (Qu et al, 2007) and it was suggested from a meta-analysis of proteomic and protein interaction data that caspase-1 cleaves its substrates to propagate inflammation to neighboring and remote cells in extracellular vesicles (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ASC specks have been shown to accumulate in the extracellular space, where they promoted IL-1b maturation (Franklin et al, 2014). Moreover, IL-1b, caspase-1, and other inflammasome components have been described to localize to exosomes (Qu et al, 2007) and it was suggested from a meta-analysis of proteomic and protein interaction data that caspase-1 cleaves its substrates to propagate inflammation to neighboring and remote cells in extracellular vesicles (Wang et al, 2016). Yet, the exact role of their presence in the compartment remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As we reported previously, for inflammation-privileged tissues, such as cardiovascular tissues in which inflammasome component genes are not constitutively expressed, TLRs work in synergy with upregulated cytosol-located sensing receptor families including NLRs (NOD (nucleotide binding and oligomerization domain)-like receptors) (30). In the cytosol, nucleus and extracellular compartment as we most recently reported, these inflammasome components and pro-caspase-1 assemble into a protein complex termed inflammasome, which subsequently activates caspase-1 after recognizing endogenous DAMPs (31). In this way, TLRs mediate upregulation, activation of a range of inflammatory genes and acceleration of vascular inflammation and atherosclerosis (2,32).…”
Section: Introductionmentioning
confidence: 99%